Pengaturan Bukti Petunjuk pada Hukum Acara Persaingan Usaha dalam Kerangka Hukum Pembuktian di Indonesia - Fendy Andih, Sterry (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 8 No 4 (2019), 2019)
Regulations related to evidence in the procedural law of business competition still cause debate because regulations related to evidence of instructions that apply in the business competition procedural law are different from the regulation of evidence in the procedural law that generally applies in Indonesia, especially if there are objections to the KPPU's decision submitted to the district court. The formulation of the problem examined is related to the procedures for resolving business competition cases by the business competition supervisory commission and the use of evidence evidence in business competition law within the criminal procedural framework in Indonesia. This type of research method used is a normative legal research method with a proof of law approach. The results of the research show that the procedure for handling cases by KPPU based on Perkom 1/2019 is sourced from KPPU's reports and initiatives. The stages or process of procedure for handling cases by KPPU consists of the initial stages (receipt of reports or KPPU initiatives), investigations, commission assembly sessions (preliminary hearing and follow-up hearings), and decisions (deliberations of commission assemblies and reading of decisions and implementing decisions) . The use of evidence of guidance in business competition law contracted in Perkom 1/2019 can still lead to this debate because the procedural law used in general courts (if there is an objection to the KPPU's decision) is criminal or civil procedural law, which if understood there are still differences fundamental evidence related to these instructions. The evidence evidence can be obtained through economic evidence and communication evidence whereas in criminal procedural law the limit is limited to evidence evidence evidence obtained from evidence witnesses, letters and statements of the defendant. Pengaturan terkait alat bukti petunjuk dalam hukum acara persaingan usaha masih menimbulkan perdebatan dikarenakan pengaturan terkait alat bukti petunjuk yang berlaku dalam hukum acara persaingan usaha berbeda halnya dengan pengaturan alat bukti petunjuk dalam hukum acara yang secara umum berlaku di Indonesia, khususnya apabila terjadi keberatan atas putusan KPPU yang diajukan kepada pengadilan negeri. Adapun rumusan permasalahan yang dikaji adalah terkait tata cara penyelesain perkara persaingan usaha oleh komisi pengawas persaingan usaha dan penggunaan bukti petunjuk pada hukum persaingan usaha dalam kerangka hukum acara pidana di indonesia. Jenis metode penelitian yang digunakan adalah metode penelitian hukum normatif dengan pendekatan hukum pembuktian. Hasil penelitian menunjukkan tata cara penanganan perkara oleh KPPU berdasarkan Perkom 1/2019 adalah bersumber dari laporan dan insiatif KPPU.  Adapun tahapan atau proses tata cara penanganan perkara oleh KPPU terdiri dari tahapan awal (penerimaan laporan atau insiatif KPPU), penyelidikan, sidang majelis komisi (sidang pemeriksaan pendahuluan dan sidang pemeriksaan lanjutan), dan putusan (musyawarah majelis komisi dan pembacaan putusan serta pelaksanaan putusan). Penggunaan bukti petunjuk pada hukum persaingan usaha yang dikontruksikan dalam Perkom 1/2019 masih dapat menimbulkan perdebatan hal ini dikarenakan hukum acara yang dipergunakan pada peradilan umum (apabila terjadi keberatan atas putusan KPPU) adalah hukum acara pidana atau perdata, yang mana apabila dipahami masih terdapat perbedaan mendasar terkait alat bukti petunjuk tersebut. Alat bukti petunjuk dapat diperoleh melalui bukti ekonomi dan bukti komunikasi sedangkan dalam hukum acara pidana dibatasi secara limitatif alat bukti petunjuk diperoleh dari alat bukti keterangan saksi, surat dan keterangan terdakwa.